2020
DOI: 10.32832/manager.v2i4.3815
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Tingkat Inflasi, Kurs, Dan Suku Bunga Bank Indonesia Terhadap Indeks Harga Saham

Abstract: Penelitian ini dilakukan untuk mengetahui pengaruh Inflasi, Kurs dan Suku Bunga Bank Indonesia periode tahun 2008 – 2018. Populasi penelitian ini adalah Bank Indonesia, Badan Pusat Statistik, Bursa Efek Indonesia. Variabel yang digunakan dalam penelitian ini adalah Inflasi, Kurs, dan Suku Bunga Bank Indonesia sebagai variabel independen; Indeks Harga Saham Gabungan sebagai variabel dependen. Analisis data yang digunakan untuk menguji hipotesis dalam penelitian ini adalah analisis regresi sederhana, analisis re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…If investors set aside some of their assets to invest in shares in the company, it will affect the profits that will be obtained later. This is in line with (Fikri et al, 2020); (Kasmir, 2021); (and Wardita et al, 2021), who discovered that Interest Rates affect Firm Value.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…If investors set aside some of their assets to invest in shares in the company, it will affect the profits that will be obtained later. This is in line with (Fikri et al, 2020); (Kasmir, 2021); (and Wardita et al, 2021), who discovered that Interest Rates affect Firm Value.…”
Section: Discussionsupporting
confidence: 84%
“…This profit decline may discourage investors from investing in the company, leading to decreased stock prices. Therefore, it can be concluded that inflation rates hurt stock returns, which is consistent with the research findings of (Fikri et al, 2020) ; (Kasmir, 2021); (Suharyanto & Zaki, 2021); (Wardita et al, 2021) which indicate that interest rates affect firm value through stock returns.…”
supporting
confidence: 86%